La conquista del paraíso o La utopía de Cristóbal Colón - Karanović, Vladimir (Verba hispanica, 2014)
The paper analyses the relationship between film and history based on the film 1492: Conquest of Paradise by Ridley Scott. It questions the importance of the context in which the movie with a historical theme is created and in that light its significance is interpreted. Based on the structural theory of myth, the article examines the elements of the mythic structure of Christopher Columbus's voyage, relating this concept to Utopia. Special emphasis is placed on the importance of the first meeting or the clash between two cultures, which determines their future relations. According to the established theoretical and critical framework, the notions of paradise as well as the figure of the foreigner are questioned. The intention of this paper is to demonstrate that in Ridley Scott's film history is much more complex and cannot be enclosed in platitudes and common places. Although it was not Scott's intention to offer a counterfactual view of recorded history, and he does not question what might have happened in other circumstances, by introducing certain apocryphal elements and foretelling later historical events, we show that he is able to start a discussion on views on the process of discovery and conquest of America and especially about their meaning throughout history and their relationship with the present.
Keywords: film; Scott, Ridley; 1942: osvojitev raja; Colombo, Cristoforo, 1451-1506; odkritje Amerike; utopija; zgodovinski filmi